Performance differences between greco-roman and freestyle wrestlers: a systematic review and meta-analysis - Ulupinar, S.; Özbay, S.; Gençoglu, C.; Ince, I. (The Journal of Strength and Conditioning Research, 2021)
This systematic review and meta-analysis aims to summarize evidence on performance differences between Greco-Roman (GR) and freestyle (Fr) wrestlers. Eleven studies met the inclusion criteria (91 individual data and a total of 752 wrestlers). The analysis of handgrip strength comprised 9 outcomes from 5 studies with no significant difference between GR and Fr wrestlers. The analysis of isometric (back or leg) strength comprised 15 outcomes from 6 studies with a significant effect favoring GR wrestlers. The analysis of muscle power comprised 15 outcomes from 5 studies with a significant effect favoring GR wrestlers. The analysis of strength endurance comprised 4 outcomes from 3 studies with no significant difference between GR and Fr wrestlers. The analysis of anaerobic capacity and power comprised 6 outcomes from 3 studies with no significant difference between GR and Fr wrestlers. The analysis of speed comprised 19 outcomes from 7 studies with a significant effect favoring GR wrestlers. The analysis of flexibility comprised 20 outcomes from 6 studies with a significant effect favoring Fr wrestlers. This study indicated that GR wrestlers had greater isometric strength, muscle power, and speed performance, but Fr wrestlers had greater flexibility. Given the significant effect sizes favoring GR wrestlers, it is possible that they focused on training strategies to improve physical strength-power performance. However, considering the significant effect size favoring Fr wrestlers, it is possible that they focused on training strategies to improve flexibility because Fr wrestling techniques require a larger range of motion during both attack and defense.